Endoplasmic Reticulum Stress Sensor IRE1α Enhances IL-23 Expression by Human Dendritic Cells - Márquez, Saioa; Fernández, José Javier; Terán-Cabanillas, Eli; Herrero, Carmen; Alonso, Sara; Azogil, Alicia; Montero, Olimpio; Iwawaki, Takao; Cubillos-Ruiz, Juan R.; Fernández, Nieves; Crespo, Mariano Sánchez (Frontiers in Immunology, 2017)
Human monocyte-derived dendritic cells (DCs) exposed to pathogen-associated molecular patterns (PAMPs) undergo bioenergetic changes that influence the immune response. We found that stimulation with PAMPs enhanced glycolysis in DCs, whereas oxidative phosphorylation remained unaltered. Glucose starvation and the hexokinase inhibitor 2-deoxy-D-glucose (2-DG) modulated cytokine expression in stimulated DCs. Strikingly, IL23A was markedly induced upon 2-DG treatment, but not during glucose deprivation. Since 2-DG can also rapidly inhibit protein N-glycosylation, we postulated that this compound could induce IL-23 in DCs via activation of the endoplasmic reticulum (ER) stress response. Indeed, stimulation of DCs with PAMPs in the presence of 2-DG robustly activated IRE1α signalling and to a lesser extent the PERK arm of the unfolded protein response (UPR). Additional ER stressors such as tunicamycin and thapsigargin also promoted IL-23 expression by PAMP-stimulated DCs. Pharmacological, biochemical, and genetic analyses using conditional knockout mice revealed that IL-23 induction in ER stressed DCs stimulated with PAMPs was IRE1α/XBP1-dependent upon zymosan stimulation. Interestingly, we further evidenced PERK-mediated and C/EBPβ-dependent trans-activation of IL23A upon LPS treatment. Our findings uncover that the ER stress response can potently modulate cytokine expression in PAMP-stimulated human DCs.